The Mediating Role of Prophetic Character in Linking Quran Memorization, Emotional Intelligence, and Student Discipline in Pesantren Indonesia - Zhafirah Syarafina; Fajri Ismail; Karoma Karoma; Indah Wigati; Maryamah Maryamah; Wildan Miftahussurur (LP. Ma'arif Janggan Magetan, 2024)
This study examines the relationships among Quran memorization activity, emotional intelligence, prophetic character, and student discipline in pesantren, with prophetic character operationalised through the FAST framework as a mediating mechanism. Employing a quantitative causal explanatory design, data were collected through a structured questionnaire administered to 95 students at Pondok Pesantren Jamiatul Qurro Palembang. Structural Equation Modelling with a partial least squares approach was used to analyse direct and indirect relationships among the variables. The findings indicate that Quran memorization activity and emotional intelligence both have significant positive effects on prophetic character and student discipline. Prophetic character emerged as the strongest predictor of discipline β = 0.412, p < .001 and significantly mediated the effects of Quran memorization β = 0.157, p = .002 and emotional intelligence β = 0.186, p < .001 on disciplined behaviour. These results suggest that discipline in religious educational settings is best understood as an internally regulated outcome shaped by moral internalisation and emotional self-regulation. The study contributes to character education literature by empirically validating prophetic character as a central mechanism linking religious practice and psychological capacity to behavioural outcomes in pesantren education.